The End of the World of Values: The Abandonment of the Axiological System in Recent Secondary World Fantasy for Young Readers. Part 1 — The Classical Model - Grzegorz Trębicki (Literatura i Kultura Popularna)
The objective of the present work (which is the first in the two-part series) is to describe the evolution of the literary genre of secondary world fantasy for young readers in reference to the axiological system that prevails in its most canonical texts. The discussion is based on a three-level axiological model previously proposed by the author. It will be first analyzed how this model functions in the classical works by J.R.R. Tolkien and Ursula K. Le Guin, and then shown how it is transformed in more recent texts. The whole process will demostrate a gradual abandonment of fantasy’s axiological and didactic ambitions.